Tumor‐Microenvironment‐Induced Degradation of Ultrathin Gadolinium Oxide Nanoscrolls for Magnetic‐Resonance‐Imaging‐Monitored, Activatable Cancer Chemotherapy. Issue 21 (14th February 2019) - Wu, Miaomiao; Xue, Yumeng; Li, Na; Zhao, Hongyang; Lei, Bo; Wang, Min; Wang, Jianwei; Luo, Meng; Zhang, Chao; Du, Yaping; Yan, Chunhua
Abstract: The development of biodegradable inorganic nanoparticles with a tumor microenvironment‐activated therapeutic mode of action is urgently needed for precision cancer medicine. Herein, the synthesis of ultrathin lanthanide nanoscrolls (Gd2 O3 NSs) is reported, which biodegrade upon encountering the tumor microenvironment. The Gd2 O3 NSs showed highly controlled magnetic properties, which enabled their high‐resolution magnetic resonance imaging (MRI). Importantly, Gd2 O3 NSs degrade in a pH‐responsive manner and selectively penetrate tumor tissue, enabling the targeted release of anti‐cancer drugs. Gd2 O3 NSs can be efficiently loaded with an anti‐cancer drug (DOX, 80 %) and significantly inhibit tumor growth with negligible cellular and tissue toxicity both in vitro and in vivo. This study may provide a novel strategy to design tumor microenvironment‐responsive inorganic nanomaterials for biocompatible bioimaging and biodegradation‐enhanced cancer therapy. Abstract : Gd2 O3 nanoscrolls have been synthesized by colloidal synthesis. This material shows tumor‐microenvironment‐induced biodegradation, allowing the targeted release of anticancer agents, significantly inhibiting tumor growth, with negligible cellular and tissue toxicity, both in vitro and in vivo.